An experimental and numerical investigation of compressive response of designed Schwarz Primitive triply periodic minimal surface with non-uniform shell thickness. (May 2020) - Jia, Heran; Lei, Hongshuai; Wang, Panding; Meng, Jinxin; Li, Chuanlei; Zhou, Hao; Zhang, Xiaoyu; Fang, Daining
Abstract: Recently, Schwarz Primitive triply periodic minimal surface (P-TPMS) structures have emerged as high-value engineering structures for a wide range of applications. The elastic modulus and ultimate strength of P-TPMS architecture are tunable and superior. Herein, the influence of structural porosity and shell thickness on the compressive response of a P-TPMS lattice structure has been separately studied. Moreover, an enhanced design method, based on local shell thickening, is proposed to obtain a lightweight structure with superior mechanical properties. A comparison between primary and enhanced architectures is carried out by using experimental characterization and finite element analysis (FEA). It has been demonstrated that the enhanced structure renders higher relative elastic modulus and ultimate strength than primary P-TPMS structures. In addition, P-TPMS structural models are reconstructed from micro X-ray tomography ( μ -CT) images and compared with as-designed models. The results reveal that selective laser sintering (SLS) is a promising fabrication route to achieve desired geometric accuracy. In addition, the comparison of experimental and FEA results indicates that the proposed enhanced design method is effective and reliable to obtain shell-based lattices with better mechanical properties.